An overview of the literature and theory of Islamic criticism, the poem "Bahri Noor" by the Kurdish poet "Mahwi" as an example. - Karzan Mohsen Qadir; Samir Ahmed Ibrahim (Zanco Journal of Humanity Sciences)
This research, titled "An overview of the literature and theory of Islamic criticism, the poem "Bahri Noor" by the Kurdish poet "Mahwi" as an example" sheds light more broadly on the literary view from the Islamic perspective, specifically with regard to literature and Islamic criticism theory. In general, reference was made in this research to the roots of these literatures, and then we discussed the theory of Islamic criticism.There is no doubt that Mahwi's poems are comprehensive and multipurpose: they include religious, mystical, philosophical, and social poetry. He composed wonderful poems for most of the subjects and poetic purposes.